Hydrogenated butadiene-p-methylstyrene block copolymer as well as preparation method and application thereof
By developing hydrogenated butadiene-p-methylstyrene block copolymers, the problems of temperature limitations and insufficient mechanical properties of existing phase change material fixtures have been solved, and copolymers with high hardness, high elastic modulus and moderate fluidity have been achieved. They are suitable for flexible phase change material fixtures in the high temperature range to meet the needs of processing weak rigid parts.
Patent Information
- Application Number
- CN202311261088.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The use temperature of existing phase change material fixtures is limited, the phase change temperature is too high or low, the fluidity is not good in the liquid phase, and the elastic modulus is not large in the solid phase, making it difficult to meet the needs of processing weak rigid parts.
A hydrogenated butadiene-p-methylstyrene block copolymer was developed to treat the butadiene-p-methylstyrene block copolymer by alkenyl selective hydrogenation to form a hydrogenated butadiene-p-methylstyrene block copolymer with excellent mechanical properties. The copolymer consists of p-methylstyrene homopolymer blocks and hydrogenated p-methylstyrene-butadiene random copolymer blocks, ensuring moderate fluidity, high hardness, high elastic modulus and high frequency impact resistance.
The hydrogenated butadiene-p-methylstyrene block copolymer has moderate fluidity, high hardness, large elastic modulus and good high-frequency impact resistance. It is suitable for flexible fixtures of phase change materials in the high temperature range, meet the needs of processing weak rigid parts, and has the characteristics of multiple reuses, no odor, and human- and environmentally friendly.
Smart Images

Figure CN119708393A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrogenated butadiene-p-methylstyrene block copolymer, in particular to a hydrogenated butadiene-p-methylstyrene block copolymer having moderate fluidity, high hardness, high elastic modulus and high use temperature and a preparation method thereof, and also to the application of the hydrogenated butadiene-p-methylstyrene block copolymer in a phase change material flexible fixture used in a weak rigidity machine part processing technology, belonging to the technical field of lithium series polymer preparation. Background Art
[0002] With the development of industry, various thin-walled, large-sized weak rigid parts are constantly used in various fields such as aerospace, automobiles, etc., and they also face the problem of how to process them. In the processing of weak rigid parts, due to the relatively low rigidity of the workpiece and poor processing technology, under the influence of cutting force, cutting vibration, cutting heat and other factors, the milling process is prone to problems such as tool deflection, deformation, vibration, etc., and the processing quality is difficult to control. In severe cases, the workpiece will be scrapped. This situation is particularly prominent in the aerospace industry.
[0003] In order to solve the processing problem of weak rigid parts in industry, repeated finishing or deformation pre-compensation are often used. However, repeated finishing and deformation pre-compensation do not change the essential characteristics of low rigidity of weak rigid parts, and the processing efficiency is low. In this case, phase change material flexible fixtures show their unique advantages as a new solution.
[0004] Machine tools are basic tools for metal processing, and machine tool fixtures are basic components of metal processing equipment. They are the interface between workpieces and machine tools, cutting tools, robots and other equipment. Their flexibility has a vital impact on modern manufacturing technology.
[0005] Flexibility generally refers to variability or adaptability. The flexibility of a fixture refers to its ability to adapt to parts of different shapes and sizes. Flexible fixtures are a large family, including modular fixtures, programmable fixtures, general flexible fixtures, phase change material flexible fixtures and other fixtures. Phase change material flexible fixtures are referred to as phase change material fixtures. The phase change materials mentioned in this article refer to those materials that can undergo solid-liquid phase transitions under certain conditions, and the phase transition is reversible. It is divided into two categories: true phase change material fixtures and pseudo phase change material fixtures.
[0006] The fixture based on phase change material has unique characteristics. Its clamping force has a large area of action and uniform clamping force. It is especially suitable for clamping workpieces with weak rigidity and complex shapes. Such workpieces are placed in the phase change material in the liquid phase and then the phase change material is quickly transformed into a solid state under certain external stimulation conditions, so that the workpiece can be evenly clamped. When the processing is completed, the phase change material is quickly changed from solid to liquid, so that the workpiece can be easily removed.
[0007] There are many phase change materials that can be used for machine tool fixtures. Various types of fixtures can be obtained by using different phase change materials, which generally include the following categories: water-ice, wax-based materials, low melting point alloys (such as lead-tin-bismuth alloys), magnetorheological materials, and electrorheological materials. The above phase change materials each have their own application characteristics and limitations.
[0008] From the perspective of the use requirements of phase change material fixtures, phase change material fixtures need to have the following characteristics: solid-liquid phase change can occur under certain conditions, good fluidity in the liquid phase, greater hardness and elastic modulus in the solid phase, good resistance to high-frequency impact, no adhesion or entanglement on the processing tools, easy to remove from the workpiece, reusable, wide temperature range in the solid phase, no odor, and friendly to people and the environment.
[0009] Styrene-based thermoplastic elastomer (SBC) is the world's largest and fastest growing thermoplastic elastomer. With its high strength, softness, rubber elasticity, small permanent deformation at room temperature, and the ability to be melted and processed like plastic at high temperatures and mixed with other materials, it has a wide range of applications in the footwear industry, plastic modification, asphalt modification, waterproof coatings, liquid sealing materials, wires, cables, automotive parts, medical device parts, household appliances, office automation and adhesives.
[0010] Para-methylstyrene, formally known as 4-methylstyrene (p-Methylstyrene, PMS), is a styrene derivative with similar chemical properties to styrene. It can be obtained through various catalytic systems to form polymethylstyrene (PPMS). Compared with polystyrene, its greatest feature is good thermal performance. Highly crystalline PPMS has higher glass transition temperature, Vicat softening point and heat deformation temperature. The glass transition temperature of PPMS is 113°C, which is 11% higher than that of polystyrene, 6% higher in Vicat softening point, and 7% higher in heat deformation temperature. Its hardness is higher than that of polystyrene, and its mechanical properties are slightly lower or basically equivalent. When copolymerized with other monomers, the copolymers show the same characteristics as the monomers, just like the copolymers of styrene. Para-methylstyrene can replace styrene in a lithium anion catalytic system to synthesize block copolymers of butadiene and para-methylstyrene. The obtained butadiene-para-methylstyrene block copolymer has a higher melting point than the butadiene-styrene block copolymer, that is, SBS.
[0011] The use temperature of styrene-based thermoplastic elastomers depends on the softening temperature of the polystyrene segment. Polymethylstyrene has a higher softening temperature than polystyrene. The block copolymers obtained by replacing styrene with p-methylstyrene and having a structure similar to SBS also have a higher softening point, that is, a higher use temperature. However, there are no reports on the successful application of hydrogenated butadiene-p-methylstyrene block copolymers as phase change material fixtures. Summary of the invention
[0012] In view of the problems that the existing phase change material fixtures have limited operating temperature, the phase change temperature is too high or too low, the fluidity in the liquid phase is poor, and the elastic modulus in the solid phase is not large, the first object of the present invention is to provide a hydrogenated butadiene-p-methylstyrene block copolymer having excellent properties such as moderate fluidity, high hardness, high elastic modulus, good high-frequency impact resistance, and a wide application temperature range.
[0013] The second object of the present invention is to provide a method for preparing the hydrogenated butadiene-p-methylstyrene block copolymer which has simple operation, low cost and mild conditions.
[0014] The third object of the present invention is to provide an application of a hydrogenated butadiene-p-methylstyrene block copolymer, which has the characteristics of good melt fluidity, high elastic modulus, high hardness, high melting temperature, etc. It is used to prepare a phase change material flexible clamp. Its comprehensive performance meets the requirements of the phase change material flexible clamp in the weak rigidity machine parts processing technology. The phase change temperature is moderate, the liquid phase has good fluidity, the solid phase has a large elastic modulus, does not adhere to the processing tool, is easy to peel and remove from the machine parts, has a wide operating temperature range, can be reused many times, has no odor, and is friendly to humans and the environment.
[0015] In order to achieve the above technical objectives, the present invention provides a hydrogenated butadiene-p-methylstyrene block copolymer, which is obtained by selectively hydrogenating a butadiene-p-methylstyrene block copolymer: the butadiene-p-methylstyrene block copolymer has the following structural expression: S1-bB / Sb-S2; wherein S1 and S2 are p-methylstyrene homopolymer blocks; B / S is a p-methylstyrene-butadiene random copolymer block; the mass proportion of S1 is 30% to 60%, and the mass proportion of S2 is 0% to 10%; the mass ratio of p-methylstyrene units to butadiene units in B / S is 1 to 5:4 to 10; the quantity ratio of 1,4-structural units to 1,2-structural units of butadiene units in B / S is 0.5 to 2:1.
[0016] The hydrogenated butadiene-p-methylstyrene block copolymer provided by the present invention has the following structure:
[0017]
[0018] Wherein, n, x, y, z and m are all polymerization degrees, wherein n, x, y and z are all integers greater than 0, m is an integer greater than or equal to 0, and y / z=0.5 to 2:1.
[0019] The hydrogenated butadiene-p-methylstyrene block copolymer provided by the present invention has a two-block or three-block structure, specifically comprising a p-methylstyrene homopolymer block I and a hydrogenated p-methylstyrene-butadiene random copolymer block, or further comprising a p-methylstyrene homopolymer block II with a shorter molecular chain, wherein the p-methylstyrene homopolymer block is a block with relatively strong rigidity, providing relatively strong hardness and relatively high melting temperature, and the hydrogenated p-methylstyrene-butadiene random copolymer block has a certain degree of randomization. The higher the degree of randomization, the closer the sequence distribution of p-methylstyrene units and hydrogenated butadiene units in the random copolymer segment is to the average distribution according to the molar ratio, which is equivalent to that the p-methylstyrene unit improves the hardness of the material while participating in the formation of the rubber segment. Of course, the addition of the p-methylstyrene unit also increases the viscosity in the molten state. By selecting an appropriate ratio of p-methylstyrene to butadiene, it can be ensured that the macroscopic physical property indicators meet the requirements. In addition, the side chain formed by hydrogenation of the 1,2-structural unit of butadiene in the hydrogenated butadiene-p-methylstyrene block copolymer is of great significance for ensuring the rubber properties. Butadiene forms 1,2-structural units and 1,4-structural units during polymerization. The 1,4-structural unit forms a polyethylene unit after hydrogenation, and the 1,2-structural unit forms a poly-1-butene unit after hydrogenation. If there is no appropriate proportion of 1,2-structural units in the butadiene unit and the 1,4-structural unit is dominant, then a polyethylene long unit will be formed after hydrogenation. The polyethylene unit crystallizes and the glass transition temperature of the entire polymer increases, and even loses the rubber properties. The alternating or random distribution of 1,2-structural units and 1,4-structural units can destroy the polyethylene crystallization that may be produced due to excessive 1,4-structures after hydrogenation. At the same time, the p-methylstyrene in the p-methylstyrene-butadiene random copolymer block is introduced into the polymer chain through a random or alternating distribution, which also destroys the crystallization of the polyethylene chain and plays the same role as the 1,2-structure. Therefore, controlling the ratio of p-methylstyrene units and butadiene units in the random copolymer segment, the sequence distribution in the chain segment, and the ratio and distribution uniformity of 1,2-structural units and 1,4-structural units are of great significance to the physical properties of the product.
[0020] As a preferred solution, the hydrogenation degree of the olefin group in the hydrogenated butadiene-p-methylstyrene block copolymer is ≥98%, and the hydrogenation degree of the benzene ring is ≤5%. The high degree of selective hydrogenation of the olefin group can give the polymer better flexibility, better processing performance, and good high-frequency impact resistance.
[0021] As a preferred solution, the number average molecular weight of the hydrogenated butadiene-p-methylstyrene block copolymer is 45,000 to 80,000, and the molecular weight distribution index is ≤1.08.
[0022] The present invention also provides a method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer. The method comprises the following steps: firstly adding p-methylstyrene monomer to an anionic polymerization system to carry out a first-stage polymerization; then adding a mixed monomer of butadiene and p-methylstyrene to carry out a second-stage polymerization; and then adding p-methylstyrene monomer to carry out a third-stage polymerization; and then subjecting the obtained glue solution to a hydrogenation reaction to obtain the hydrogenated butadiene-p-methylstyrene block copolymer.
[0023] As a preferred solution, butadiene and p-methylstyrene are fully mixed to form a uniform mixed monomer, which is then added to an anionic polymerization system for two-stage polymerization. The highly uniformly mixed butadiene monomer and p-methylstyrene monomer participate in the copolymerization reaction, which is beneficial to improving the degree of random copolymerization.
[0024] As a preferred solution, butadiene monomer and p-methylstyrene mixed monomer are obtained by mixing by the following method: 1) vacuuming the inside of sealed tank I and injecting p-methylstyrene monomer into the sealed tank I; 2) vacuuming the inside of sealed tank II and injecting butadiene monomer into the sealed tank II; 3) using nitrogen to press the p-methylstyrene monomer in sealed tank I into the sealed tank II, and using the nitrogen pressure in sealed tank II to fully mix the p-methylstyrene monomer and the butadiene monomer, or, using nitrogen to press the butadiene monomer in sealed tank II into the sealed tank I, and using the nitrogen pressure in sealed tank I to fully mix the butadiene monomer and p-methylstyrene monomer.
[0025] As a preferred solution, the nitrogen pressure of the sealed tank I or sealed tank II is maintained at 0.4-0.6 MPa.
[0026] As a preferred solution, the butadiene and p-methylstyrene mixed monomers are added all at once, in batches, or slowly and continuously.
[0027] As a preferred solution, the anionic polymerization system comprises a non-polar alkane solvent, an initiator and a randomizing agent.
[0028] As a preferred solution, the non-polar alkane solvent is cyclohexane; the amount of cyclohexane used maintains the mass percentage concentration of the polymerized monomers in the anionic polymer system within the range of 5 to 15%.
[0029] As a preferred solution, the initiator is n-butyl lithium. Alkyl lithium or aryl lithium commonly used in the art can meet the application requirements.
[0030] As a preferred solution, the randomizing agent is at least one of ditetrahydrofurfuryl propane, tetramethylethylenediamine, tetrahydrofurfuryl alcohol ethyl ether, and tetrahydrofuran. The randomizing agent can be used to adjust the degree of random copolymerization of butadiene and p-methylstyrene. Adding the randomizing agent to the polymerization not only changes the polymerization rate of p-methylstyrene and butadiene during copolymerization and affects the sequence distribution of p-methylstyrene and butadiene, but also plays a role in increasing the dissociation of the catalyst and adjusting the ratio of 1,2-structural units and 1,4-structural units of butadiene, and the dissociation of the catalyst is beneficial to improving the efficiency of the catalyst.
[0031] As a preferred solution, the amount of the randomizing agent used in the non-polar alkane solvent is 50 to 280 mg / kg.
[0032] As a preferred scheme, during the first stage polymerization, the second stage polymerization and the third stage polymerization reaction, the pressure is maintained in the range of 0.1MPa to 0.5MPa, the first stage polymerization temperature is 60°C to 70°C, the time is 25 to 50min, the second stage polymerization temperature is 60 to 80°C, the time is ≥50min (until the reaction is complete), and the third stage polymerization temperature is 60°C to 70°C, and the time is greater than 15min.
[0033] As a preferred solution, the conditions of the hydrogenation reaction are: hydrogen pressure of 1.0-2.0 MPa, hydrogenation reaction temperature of 70-75° C., and time of 1.5-2.5 h.
[0034] As a preferred solution, a dicyclopentadiene titanium dichloride / dimethyl phthalate combined hydrogenation catalyst is used in the catalytic reaction process.
[0035] In the hydrogenation reaction process of the present invention, the rubber is pressed into a hydrogenation kettle replaced by nitrogen, the temperature is raised to 70-75° C., a co-catalyst dimethyl phthalate is first added for passivation reaction for 5-15 minutes, and then a main catalyst dicyclopentadiene titanium dichloride is added, and a hydrogenation reaction is carried out under a hydrogen pressure of 1.0-2.0 MPa for 1.5-2.5 hours. The hydrogenation degree of the alkenyl group in the polymer is ≥98%, and the hydrogenation degree of the benzene ring is ≤5%.
[0036] The hydrogenated butadiene-p-methylstyrene block copolymer prepared by the present invention needs to remove metal ions. The main process is: firstly, a small amount of soft water is used to terminate the reaction of hydrogenated glue solution for 15 minutes, then it is acidified with tert-butyl ...
[0037] The present invention also provides an application of a hydrogenated butadiene-p-methylstyrene block copolymer, which is used for preparing a phase change material flexible fixture, in particular a phase change material flexible fixture used in a weak rigidity machine part processing process.
[0038] As a preferred solution, the hydrogenated butadiene-p-methylstyrene block copolymer is melt-mixed with oil and / or solid organic matter.
[0039] As a preferred solution, the mass percentage composition of the hydrogenated butadiene-p-methylstyrene block copolymer and the oil product and / or solid organic matter is 20-50%:50-80%.
[0040] As a preferred solution, the oil product includes saturated liquid hydrocarbons; and the solid organic matter includes saturated solid hydrocarbons or saturated fats.
[0041] The main component of the solid organic matter in the technical solution of the present invention is a saturated organic matter, for example, it can be a hydrocarbon solid mixture mainly composed of straight-chain alkanes, preferably No. 58 paraffin, or a low-melting-point solid organic matter containing other elements, such as polyethylene wax, stearic acid, etc., preferably polyethylene wax. The main component of the oil product is a liquid hydrocarbon mixture mainly composed of straight-chain alkanes, preferably cosmetic grade No. 26 white oil, or a cycloalkane oil whose main component is saturated cycloalkane, and the preferred solution is KN4003.
[0042] The technical solution of the present invention preferably comprises cosmetic grade No. 26 white oil and No. 58 paraffin in the following mass percentages: 20-60% of No. 58 paraffin, 20-50% of cosmetic grade No. 26 white oil, and 20-50% of the copolymer, and mixes them together according to the above proportions, heats them until the mixture melts, stirs them evenly while heating, and cools them naturally to a solid state to obtain a mixed material.
[0043] The hydrogenated butadiene-p-methylstyrene block copolymer provided by the technical solution of the present invention can be evenly melt-mixed with other conventional materials to prepare a phase change material flexible fixture, which is applied to the processing technology of weak rigid parts. Compared with existing paraffin, low melting point metals, urea, water-ice and other materials, it has better fluidity in liquid state, large elastic modulus in solid state, wide temperature adaptability range, good high-frequency impact resistance, no adhesion, no entanglement with tools and workpieces, easy removal, no odor, can be reused many times, is harmless to the human body, and is environmentally friendly.
[0044] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0045] 1. The hydrogenated butadiene-p-methylstyrene block copolymer provided by the present invention has a special molecular structure, with asymmetric p-methylstyrene blocks at both ends and a random copolymerization section of p-methylstyrene and butadiene in the middle, and the polybutadiene unit contains a suitable proportion of 1,2-structural units, and the butadiene unit is highly hydrogenated. This special molecular structure gives the polymer good comprehensive mechanical properties, especially good fluidity in the molten state, high hardness and elastic modulus in the solid state, good resistance to high-frequency impact, and is very suitable as a phase change material flexible fixture after melt blending with other materials, and is used for the processing of weak rigid parts. It has the advantages of good fluidity in the liquid state, high hardness and elastic modulus in the solid state, non-adhesion, winding processing tools, wide operating temperature range, harmlessness to the human body, environmental friendliness, and reusability.
[0046] 2. The hydrogenated butadiene-p-methylstyrene block copolymer of the present invention has three outstanding advantages: First, the middle section of the co-block polymer is a special structure of a random copolymer section of p-methylstyrene and butadiene. The random copolymer section of p-methylstyrene and butadiene ensures that the elastomeric characteristics can be maintained when the total mass percentage of p-methylstyrene in the copolymer exceeds 50%, which is also one of the reasons why the copolymer has good hardness and high elastic modulus in the solid state, and also makes the copolymer have a higher use temperature; second, the molecular weight of the p-methylstyrene block at both ends is asymmetric, one end has more and the other end has less. The end with less content cannot aggregate into PPMS phase due to its small content and cannot provide crosslinking points, so that the material does not have certain tensile properties like ordinary thermoplastic rubber. This feature Together with the characteristic of molecular weight between 45,000 and 80,000, it has the advantage of not adhering to or entangled with processing tools when used as a phase change material flexible fixture. Thirdly, the copolymer has a high content of p-methylstyrene, with a portion of it forming p-methylstyrene blocks at both ends and a portion of it being randomly copolymerized with butadiene as the second segment. This characteristic, together with the characteristic that 1,4-structural units in butadiene become polyethylene plastics after hydrogenation and 1,2-structural units become poly-1-butene rubber after hydrogenation, makes it a phase change material flexible fixture with good hardness and elastic modulus in the solid state, and resistance to high-frequency impact. When weak rigid parts are processed by high-speed rotating tools, it can ensure that the parts do not move and eliminate possible cutting chatter to ensure processing accuracy.
[0047] 3. Compared with similar polymers with random copolymer structure, the hydrogenated butadiene-p-methylstyrene block copolymer with block structure of the present invention has higher hardness, larger elastic modulus and better high-frequency impact resistance. Both structures have their own applicable scope.
[0048] 4. The preparation method of the hydrogenated butadiene-p-methylstyrene block copolymer of the present invention is simple, low in cost, and has mild process conditions, thus meeting the requirements for industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is the GPC chart of the non-hydrogenated block copolymer. DETAILED DESCRIPTION
[0050] In order to further illustrate the details of the present invention, several embodiments are listed. The following embodiments are intended to illustrate the contents of the present invention, rather than to limit the scope of protection of the claims of the present invention.
[0051] Analysis method: Molecular weight and molecular weight distribution are determined by gel permeation chromatography; melt index test is carried out according to GB / T 3682-20008; hardness is in accordance with GB / T 2411-2008; 1,2-structure and 1,4-structure content are determined according to HNMR analysis results.
[0052] In the following examples, butadiene monomer and p-methylstyrene monomer are uniformly mixed by the following method: 1) negative pressure is evacuated inside sealed tank I, and p-methylstyrene monomer is injected into the sealed tank I; 2) negative pressure is evacuated inside sealed tank II, and butadiene monomer is injected into the sealed tank II; 3) the p-methylstyrene monomer in sealed tank I is pressed into the sealed tank II by nitrogen, and the p-methylstyrene monomer and butadiene monomer are fully and uniformly mixed by the nitrogen pressure (about 0.5 MPa) in sealed tank II.
[0053] Example 1
[0054] A base rubber with a number average molecular weight of 50,000, a first-stage p-methylstyrene content of 40%, a second-stage p-methylstyrene content of 20%, butadiene 35%, and a third-stage p-methylstyrene content of 5% was prepared and then hydrogenated.
[0055] 3000 ml of pure cyclohexane (water value < 20 ppm) and 3.0 ml of ditetrahydrofurfuryl propane (prepared into 0.5 mol / L cyclohexane solution, the amount is equivalent to 120 mg / kg solvent) were added to a 5-liter polymerization kettle replaced with high-purity nitrogen, stirring was started, the temperature was raised to 60°C, and then 178 ml of p-methylstyrene monomer and 8.0 mmol of n-butyl lithium were added respectively, and the polymerization reaction lasted for 30 minutes, and then 225 ml of butadiene and 89 ml of p-methylstyrene mixed monomer were added. The mixed monomer was added to the polymerization kettle in a one-time manner, and the reaction temperature was controlled below 80°C. After the reaction lasted for 60 minutes, 22 ml of p-methylstyrene monomer was added, and the reaction lasted for 30 minutes at a temperature of 60-65°C. After the polymerization reaction was completed, the glue solution was introduced into a 5-liter hydrogenation kettle, the temperature was raised to 70°C, 12 mmol of n-butyl lithium was added, and the reaction was terminated with hydrogen for 10 minutes. Add 10mmol of cocatalyst dibutyl phthalate and 0.5g of main catalyst dicyclopentadiene titanium dichloride, control the hydrogenation pressure at 1.0-1.5MPa, and perform hydrogenation reaction for two hours, add cocatalyst 2-3 times in the middle, each time 2mL. After the hydrogenation reaction is completed, transfer the hydrogenated glue to a water washing kettle, heat to 60-65°C, terminate the hydrogenated glue reaction with 20mL of soft water for 15min, then acidify with 5mL of tert-butyl phthalic acid (dissolved in 200mL of cyclohexane) for 30min, emulsify and extract with 300mL of soft water for 15min, centrifuge and stand, separate the water phase, repeat 2 times, condense the remaining glue through water vapor, and dry to obtain hydrogenated p-methylstyrene-p-methylstyrene / butadiene-p-methylstyrene copolymer.
[0056] The performance test results are as follows:
[0057] The GPC analysis results show that the number average molecular weight of the base rubber is 53,000 and the molecular weight distribution is 1.03;
[0058] HNMR analysis results: the 1,2-structure content of the block copolymer base rubber PB segment is 35.72%;
[0059] Iodine value analysis results: hydrogenation degree is 98.3%;
[0060] Due to performance requirements, the elastomer properties do not require tensile properties, and only the melt index and hardness are measured. The Shore A hardness is 79 and the melt index is 15.2g / 10min.
[0061] According to the mass ratio of 40% of the prepared hydrogenated butadiene-p-methylstyrene block copolymer, 25% of No. 58 paraffin and 35% of No. 26 white oil, they are mixed, heated to melt, mixed evenly and then cooled to a solid state. The Shore A hardness is 89. When used in the flexible fixture of phase change materials, it does not adhere to or entangle the tool, and the workpiece does not vibrate or move during processing.
[0062] High temperature aging resistance test method: Heat to liquid state, then naturally cool to solid room temperature, repeat 10 times, and judge the high temperature aging resistance based on the material appearance color and the use of the phase change material flexible fixture.
[0063] The experimental results are summarized in Table 1.
[0064] Example 2
[0065] The specific preparation process is the same as that in Example 1.
[0066] A base rubber with a number average molecular weight of 45,000, a first-stage p-methylstyrene content of 50%, a second-stage p-methylstyrene content of 20%, butadiene 30%, and a third-stage p-methylstyrene content of 0% was prepared and then hydrogenated.
[0067] The formula for preparing a flexible fixture for phase change material is 30% by mass of hydrogenated butadiene-p-methylstyrene block copolymer, 40% of No. 58 paraffin, and 30% of No. 26 white oil. It is used as a flexible fixture for phase change material and subjected to high temperature aging resistance experiments.
[0068] The experimental results are shown in Table 1.
[0069] Example 3
[0070] The specific preparation process is the same as that in Example 1.
[0071] A base rubber with a number average molecular weight of 80,000, a first-stage p-methylstyrene content of 45%, a second-stage p-methylstyrene content of 20%, butadiene 30%, and a third-stage p-methylstyrene content of 5% was prepared and then hydrogenated.
[0072] The mixed material formula includes 35% by weight of hydrogenated butadiene-p-methylstyrene block copolymer, 25% by weight of No. 58 paraffin wax, and 40% by weight of No. 26 white oil. Other aspects are the same as those in Example 1.
[0073] Example 4
[0074] The specific preparation process is the same as that in Example 1.
[0075] A base rubber with a number average molecular weight of 70,000, a first-stage p-methylstyrene content of 45%, a second-stage p-methylstyrene content of 10%, butadiene 45%, and a third-stage p-methylstyrene content of 0% was prepared and then hydrogenated.
[0076] The mixed material formula is as follows: the mass ratio of hydrogenated butadiene-p-methylstyrene block copolymer is 40%, No. 58 paraffin is 40%, and No. 26 white oil is 20%. Others are the same as in Example 1.
[0077] Comparative Example 1
[0078] A base rubber with a number average molecular weight of 50,000, a first-stage p-methylstyrene content of 40%, a second-stage p-methylstyrene content of 20%, butadiene 35%, and a third-stage p-methylstyrene content of 5% was prepared and then hydrogenated.
[0079] The preparation process is the same as in Example 1, except that no structure regulator is added during polymerization.
[0080] The formula for preparing the flexible fixture of phase change material is 30% by mass of hydrogenated butadiene-p-methylstyrene block copolymer, 45% of No. 58 paraffin, 35% of No. 26 white oil,
[0081] The obtained hydrogenation product is a plastic-like material, and a phase change material flexible clamp cannot be obtained.
[0082] The experimental results are shown in Table 1
[0083] Comparative Example 2
[0084] The preparation process is the same as that of Example 1.
[0085] A base rubber with a number average molecular weight of 80,000, a first-stage p-methylstyrene content of 25%, a second-stage p-methylstyrene content of 20%, butadiene 30%, and a third-stage p-methylstyrene content of 25% was prepared and then hydrogenated.
[0086] The formula for preparing the phase change material flexible fixture is 35% by mass of SEBS, 35% of No. 58 paraffin, and 30% of No. 26 white oil. The experimental results are shown in Table 1:
[0087] Table 1: Application of various copolymers and phase change materials flexible clamps with different structures
[0088]
[0089]
Claims
1. A hydrogenated butadiene-p-methylstyrene block copolymer, characterized in that: The butadiene-p-methylstyrene block copolymer is obtained by selective hydrogenation of the olefin group: The butadiene-p-methylstyrene block copolymer has the following structural expression: S1-bB / Sb-S2; in, S1 and S2 are p-methylstyrene homoblocks; B / S is a random copolymer of p-methylstyrene and butadiene; The mass proportion of S1 is 30% to 60%, and the mass proportion of S2 is 0% to 10%; The mass ratio of p-methylstyrene units to butadiene units in B / S is 1-5:4-10; The quantity ratio of 1,4-structural units to 1,2-structural units of butadiene units in B / S is 0.5 to 2:
1.
2. A hydrogenated butadiene-p-methylstyrene block copolymer according to claim 1, characterized in that: The hydrogenation degree of the alkenyl groups in the hydrogenated butadiene-p-methylstyrene block copolymer is ≥98%, and the hydrogenation degree of the benzene ring is ≤5%.
3. A hydrogenated butadiene-p-methylstyrene block copolymer according to claim 1 or 2, characterized in that: The number average molecular weight is 45,000 to 80,000, and the molecular weight distribution index is ≤1.
08.
4. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to any one of claims 1 to 3, characterized in that: In an anionic polymerization system, firstly add p-methylstyrene monomer to carry out one-stage polymerization; then add butadiene and p-methylstyrene mixed monomer to carry out two-stage polymerization; then add p-methylstyrene monomer to carry out three-stage polymerization; the glue obtained by the two-stage polymerization or the three-stage polymerization is subjected to hydrogenation reaction to obtain the product.
5. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 4, characterized in that: Butadiene and p-methylstyrene are fully mixed to form a uniform mixed monomer, which is then added into an anionic polymerization system for two-stage polymerization.
6. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 5, characterized in that: The butadiene monomer and the p-methylstyrene monomer are mixed by the following method: 1) vacuuming the inside of sealed tank I to a negative pressure, and injecting p-methylstyrene monomer into the sealed tank I; 2) vacuuming the inside of sealed tank II to a negative pressure, and injecting butadiene monomer into the sealed tank II; 3) using nitrogen to press the p-methylstyrene monomer in sealed tank I into the sealed tank II, and using the nitrogen pressure in sealed tank II to fully mix the p-methylstyrene monomer with the butadiene monomer, or, using nitrogen to press the butadiene monomer in sealed tank II into the sealed tank I, and using the nitrogen pressure in sealed tank I to fully mix the butadiene monomer with the p-methylstyrene monomer.
7. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 6, characterized in that: The nitrogen pressure of the sealed tank I or sealed tank II is maintained at 0.4-0.6 MPa.
8. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 4, characterized in that: The butadiene and p-methylstyrene mixed monomers are added in a manner of all-at-once, batchwise or slowly and continuously.
9. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 4, characterized in that: The anionic polymerization system comprises a non-polar alkane solvent, an initiator and a randomizing agent.
10. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 9, characterized in that: The non-polar alkane solvent is cyclohexane; The amount of cyclohexane used maintains the total mass percentage concentration of the polymerized monomers in the anionic polymer system within the range of 5 to 15%; The initiator is n-butyl lithium; The randomizing agent is at least one of ditetrahydrofurfuryl propane, tetramethylethylenediamine, tetrahydrofurfuryl alcohol ethyl ether and tetrahydrofuran; The randomizing agent is used in an amount of 50 to 280 mg / kg relative to the non-polar alkane solvent.
11. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 4, characterized in that: During the first stage polymerization, second stage polymerization and third stage polymerization reaction processes, the pressure is maintained in the range of 0.1MPa to 0.5MPa, the temperature of the first stage polymerization is 60°C to 70°C, the time is 25 to 50min, the temperature of the second stage polymerization is 60 to 80°C, the time is ≥50min, and the temperature of the third stage polymerization is 60°C to 70°C, and the time is not less than 15min.
12. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 4, characterized in that: The conditions of the hydrogenation reaction are: hydrogen pressure of 1.0-2.0 MPa, hydrogenation reaction temperature of 70-75° C., and time of 1.5-2.5 h.
13. The method for preparing a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 4 or 12, characterized in that: In the catalytic reaction process, a combined hydrogenation catalyst of dicyclopentadiene titanium dichloride / dimethyl phthalate is used.
14. The use of a hydrogenated butadiene-p-methylstyrene block copolymer according to any one of claims 1 to 3, characterized in that: Used to prepare flexible fixtures of phase change materials.
15. The use of a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 14, characterized in that: The hydrogenated butadiene-p-methylstyrene block copolymer is melt-mixed with oil and / or solid organic matter.
16. The use of a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 15, characterized in that: The mass percentage composition of the hydrogenated butadiene-p-methylstyrene block copolymer and the oil product and / or solid organic matter is 30-45%:55-70%.
17. The use of a hydrogenated butadiene-p-methylstyrene block copolymer according to claim 16, characterized in that: The oil products include saturated liquid hydrocarbons; the solid organic matter includes saturated solid hydrocarbons or saturated fats.
Citation Information
Patent Citations
Preparation method of linear styrene type thermoplastic elastic bodies
CN102702456A
A hydrogenated styrene-b-styrene / butadiene-b-styrene copolymer, an elastomer wire material, a preparing method of the copolymer and applications of the elastomer wire material
CN107540799A
Preparation method of high-thermal-conductivity flexible phase-change material and battery module
CN111607362A
Transparent, impact-resistant polystyrene on styrene-butadiene block copolymer basis
CN1345343A
Transparent styrol-butadiene block copolymer mixtures
CN1596285A